A New Biocomputing Platform Based on Potential- and pH-Sensitive Bioelectrocatalysis and Layer-by-Layer Films Assembled with Graphene Derivatives and Weak Polyelectrolyte. (1st December 2016) - Li, Menglu; Yu, Xue; Liu, Hongyun
Graphical abstract: Binary and ternary logic gates were fabricated on the same platform on the basis of potential- and pH-controllable bioelectrocatalysis and layer-by-layer films assembled with graphene derivatives and weak polyelectrolyte. Highlights: A new biocomputing platform was established based on potential- and pH-switched bioelectrocatalysis behaviors of (PAH/GO)3 films. Binary logic circuits with 3-input/4-output and a decimal parity checker were constructed. A mimic ternary INHIBIT logic gate based on enzymes and graphene derivatives was reported for the first time. Abstract: In the present work, (PAH/GO)n layer-by-layer (LbL) films have been assembled on the surface of electrodes based on the electrostatic interaction between graphene oxide (GO) and polyallylamine (PAH). At the LbL film electrodes, the electroactive probe K3 Fe(CN)6 in buffers demonstrates potential-sensitive cyclic voltammetric (CV) behavior because of the transition between GO and its reduced form (rGO) in the films at different potentials. K3 Fe(CN)6 in buffers also shows pH-responsive CV behavior in the LbL films, due to the electrostatic interactions between the films and the probe at different pH. The multiple-stimuli CV properties of the system are used as the potential- and pH-responsive ON-OFF switches and further utilized to perform the electro-reduction of H2 O2 catalyzed by horseradish peroxidase (HRP) and mediated by the probe in solution. With the same platform, a connected logic gate network with 3 inputs and 4 outputs, a decimal parity checker, and a ternary INHIBIT logic gate, are fabricated. This work provides the first example of how to construct a multi-valued logic gate system on the foundation of graphene derivatives and enzymatic catalytic reactions. It opens a new possibility to mimic multi-functioned logic networks by using bioelectrocatalytic platform.